2020
DOI: 10.1039/c9ra09546b
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the effect of precursor decomposition time on the structural and optical properties of copper(i) nitride nanocubes

Abstract: To study the effect of time on the colloidal synthesis of Cu3N nanoparticles, copper(ii) nitrate was thermally decomposed at 260 °C for up to 60 min in octadecylamine as a stabilizing ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…This growth mechanism was later confirmed under slightly different conditions. 121 In addition, long reaction times (at 260 °C) lead to the decomposition of the formed Cu 3 N to Cu(0) particles. Xi et al also studied the magnetic properties of the Cu 3 N NCs and observed paramagnetic and ferromagnetic contributions.…”
Section: Copper Nitridementioning
confidence: 99%
“…This growth mechanism was later confirmed under slightly different conditions. 121 In addition, long reaction times (at 260 °C) lead to the decomposition of the formed Cu 3 N to Cu(0) particles. Xi et al also studied the magnetic properties of the Cu 3 N NCs and observed paramagnetic and ferromagnetic contributions.…”
Section: Copper Nitridementioning
confidence: 99%
“…More recently, however, there has been added interest in the synthesis of different types of Cu 3 N nanostructures [ 36 , 37 ]. A flurry of different synthesis routes was applied to synthesise nitride nanoparticles, for example by solvothermal methods using copper azide in toluene or THF at moderate temperature [ 38 ], by thermal decomposition of Cu(NO 3 ) 2 in solutions containing long chain amines as solvents and capping agents [ 39 , 40 , 41 ], via the reaction of copper(II) acetate with NH 3 gas in long-chain alcohol solvents [ 42 ] by a one-step process in which copper(II) methoxide reacts with benzylamine [ 43 ] or by reduction of Cu(II) to Cu(I) combined with nitridation of Cu(I) by hexamethylenetetramine [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the development of facile, inexpensive synthetic methods is especially valuable given the emerging commercial applications of nanomaterials. Synthesis using long-chain amines [ 39 , 40 , 41 ] is becoming the most-utilized chemical method for the fabrication of Cu 3 N nanopowders. Implementing this route on a commercial basis is challenging, however, due both to the costs of the required chemicals and to the limits of morphological control that can be exerted [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkylamines have been used as reducing agents, 54,55 or as a source of ammonia. 50 Certain side reactions were reported, such as the oxidation to nitriles, 47,56,57 or the condensation with carboxylic acids. 53 However, none of these previously reported transformations yielded byproducts with high binding affinity for the NC surface.…”
mentioning
confidence: 99%